Classification of individual managers' systems thinking skills based on different organizational ownership structures. (16th February 2021) - Nagahi, Morteza; Hossain, Niamat Ullah Ibne; Jaradat, Raed; Dayarathna, Vidanelage; Keating, Chuck; Goerger, Simon; Hamilton, Michael
Abstract: The current body of literature lacks studies related to organizational managers' classification of systems thinking (ST) skills based on both their overall systemic tendency and the organizational ownership structure. The purpose of this study is to assess and classify the ST skills of senior managers who currently work in a complex business environment. Initially, we clustered managers' overall systemic thinking (OST) using the Bayesian latent class analysis (BLCA) method into two distinct clusters: managers with upper OST (holistic thinker) and managers with lower OST (reductionist thinker). Further, we classified managers' ST skills into two predefined classes to understand the characteristics of each group better. A total of 51 senior managers from two different organizational structures participated in this study. Results show that the ST skills of managers in public are more towards the upper OST/holistic cluster, whereas managers from the private sector have an inclination towards lower OST/reductionist cluster.